(untitled) (Journal of history, 2020)
This article is devoted to the problem of researching value of «usun». Researches of history usun’s tribes living in III – I centuries, it is one of issues of the day for Kazakh history. Because, many researchers in area of history, unanimously, agree with opinion that usuns are early ancestors of not only Kazakhs but also other turkic people of Middle Asia and matter very much in history of ancient turkic ethnic clans. The article is considered such questions as origin, location, relationships with neighboring countries of ancient usuns. Authors are studying labours of well-known scientists, such as N.A. Aristov, U.A. Zuyev, V.V. Vostrov and M.S. Mukanov, I. Kabyshuly, N. Mynzhanuly, N. Mukametuly, aimed to do an all-round analysis about the origin of value of «usun». Key words: value of «usun», researches, Chinese writing sourses, word «usun», archaeological materials.